Conceptual Change in Life Sciences Learning: The Impact of Teaching Tools on Knowledge Representation - Mhlongo, Thabo; Sedumedi, Thomas Dipogiso (Indonesian Journal of Science and Mathematics Education, 2023)
This article explores the impact of tool-method combinations on conceptual changes, comparing the use of interactive whiteboards (TFM-IWBs) and traditional blackboards (TFM-TBBs). These combinations are integrated with traditional teaching methods (TFM) for educational purposes, focusing on natural science topics in Grade 9. The study analyzes specific changes in knowledge representation using qualitative approaches and a quasi-experimental design. The results show student knowledge structure variations depending on the tool-method combination used. The TFM-TBB combination primarily affects declarative knowledge, while TFM-IWB more significantly influences procedural and conditional knowledge. Hence, there is an impact of tool-method combinations on conceptual changes. This research recommends further investigating how different tool-method combinations affect learning outcomes across various subjects and educational levels.